Indigenous knowledge systems as a catalyst for inclusive self-directed learning in rural South African secondary schooling: Evidence from a mixed-methods case study - Setsubi, Dieketseng Olga Letittia; Seleke, Benjamin (Edelweiss Applied Science and Technology, 2026)
South African curriculum policy recognizes indigenous knowledge systems (IKS) and commits schooling to inclusive, socially responsive learning, yet rural schools often struggle to operationalize these aims. This article synthesizes evidence from a convergent mixed-methods single-case study in a rural secondary school in the Alfred Nzo West District (Eastern Cape) to examine how IKS integration relates to inclusive participation and self-directed learning (SDL). Qualitative data (semi-structured interviews with teachers, parents, and community elders; a learner focus group) and quantitative questionnaire indicators were collected concurrently and analyzed using thematic analysis and descriptive statistics, then triangulated. Findings suggest that locally grounded IKS examples increased learner engagement, broadened participation, and supported SDL behaviors, including questioning, goal-setting during inquiry, peer explanation, and reflection. Implementation, however, was constrained by limited teacher professional development, insufficient learning materials and time, and gaps between policy intent and school-level enactment. The article proposes an IKS-enabled implementation pathway to guide systematic integration through community knowledge mapping, curriculum alignment, inclusive lesson design, learner-led inquiry, and iterative assessment. The study argues that IKS can function as an applied pedagogical design strategy for inclusion and learner agency when aligned with coherent professional learning and context-appropriate resources.